Study on the Mechanism of Flos Carthami Treatment for Chronic Alcoholic Liver Injury Using BP Neural Network Algorithm Combined with UHPLC-MS Technology - Xi-ye WANG; Xiao-jing HAN; Ming-yang JIANG; Mei-rong BAI; Liang XU (Zhipu Xuebao)
Flos Carthami (FC) has a good therapeutic effect on chronic alcoholic liver injury (CALI) in clinical practice, but the treatment mechanism is not very clear. Therefore, elucidating the molecular mechanism of action of FC in treating CALI is of great significance for the further development and application of drugs. Male Wistar rats were as the research object. The model group rats were orally administered with 8 mL/kg alcohol for 28 days to establish a CALI model, while the treatment group rats were orally administered with high (4.2903 g/kg), medium (1.4301 g/kg), and low (0.4767 g/kg) doses of FC extract. Potential biomarkers related to CALI were identified using rat serum metabonomics analysis methods combined with ultra-high performance liquid chromatography mass spectrometry (UHPLC-MS) technology, and the regulatory mechanisms of FC on these biomarkers were investigated. The BP neural network model was established by MATLAB software to deal with the classification problem of omics data. The H&E staining experiment found that after gavage, high-dose FC extract can reduce the degree of liver cell damage. Compared with the model group, the expression levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in the high-dose FC group decrease, indicating that the high-dose FC extract has liver protective effect. The classification accuracy of the BP neural network model is 95.8%, and the classification effect is good. Through volcanic map analysis, a total of twenty biomarkers related to CALI are identified, and FC can have a callback effect on these biomarkers. The results indicated that FC may exert therapeutic effect on CALI by regulating the metabolism of triglycerides, fatty acids, phospholipids, bile acids, amino acids and Vitamin E. This study provides a theoretical foundation for the promotion and clinical application.